Communication, Information and Education Services Related to Adherence to Taking Medication in Type 2 Diabetes Mellitus Patients at H. Adam Malik Central General Hospital Medan - Eva Sartika Dasopang; Desy Natalia Siahaan; Thalita Sandika; Yelda Ratu Thaharah; Nadia Nuzulia; Verawati Lince (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
One of the standards for clinical pharmacy services in hospitals is related to communication, information, and education. Blood sugar levels in Diabetes Mellitus patients are strongly influenced by lifestyle, calorie consumption, and drugs consumed. The purpose of this study was to determine the provision of Communication, Information and Education services on Adherence to Taking Medication in Type 2 Diabetes Mellitus Patients at the H. Adam Malik Medan Central General Hospital. This research is a quantitative descriptive type research. The research was conducted at the H. Adam Malik Medan Central General Hospital, which was conducted from March 2023 to June 2023. The population used in this study were patients with type 2 diabetes mellitus from March 2023 to June 2023. Sampling using purposive sampling technique. The research sample amounted to 100 people. The research instrument used a questionnaire. Data analysis using univariate analysis with descriptive, data processing with Statistical Product and Service Solution (SPSS) software version 20. The results showed that Communication, Information and Education services by Doctors as many as 94 people (94%), Pharmacists as many as 5 people (5%), and Nurses as many as 1 person (1%) and adherence to taking medication in Type 2 Diabetes Mellitus (DM) patients were found that 60 respondents (60%) were classified as moderate adherence, 40 respondents (40%) were classified as low adherence. Pharmacists should be able to improve their knowledge, abilities, and skills in conducting Communication, Information, and Education Services so that patients are more compliant in the treatment of Diabetes Mellitus. Keyword: Communication, Diabetes Mellitus type 2, Education, Information, Service